2011
DOI: 10.1124/jpet.111.185892
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Myocardial Gene Alterations Associated with Doxorubicin-Induced Cardiotoxicity in Rats Persist for 2 Months after Treatment Cessation

Abstract: The molecular mechanisms underlying doxorubicin (DOX)-induced cardiomyopathy include alterations in cardiomyocytes' oxidative stress status and in gene expression. Although such alterations have been reported during in vivo DOX treatment of animals, it remains to be clarified whether they persist after treatment cessation. To address this question, rats were injected with either saline (1 ml/kg/day i.p; control) or DOX (1 mg/kg/day i.p.) for 10 days, and 70 days later cardiac functional parameters were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 37 publications
8
25
0
1
Order By: Relevance
“…Recent studies suggested that oxidative stress could be a late event in anthracycline cardiotoxicity, according to the results, which demonstrated an increased superoxide production in the heart 2 months after DOX treatment (cumulative dose 10 mg/kg). On the contrary, 8 days after DOX administration, no signs of oxidative stress were observed [23]. Our results showing an up-regulation of gp91phox and a down-regulation of Abcb8 in the subchronic DAU model are in agreement with the data of these authors.…”
Section: Discussionsupporting
confidence: 95%
“…Recent studies suggested that oxidative stress could be a late event in anthracycline cardiotoxicity, according to the results, which demonstrated an increased superoxide production in the heart 2 months after DOX treatment (cumulative dose 10 mg/kg). On the contrary, 8 days after DOX administration, no signs of oxidative stress were observed [23]. Our results showing an up-regulation of gp91phox and a down-regulation of Abcb8 in the subchronic DAU model are in agreement with the data of these authors.…”
Section: Discussionsupporting
confidence: 95%
“…DOX has been consistently found to decrease SERCA2a mRNA and protein levels (Arai et al, 1998;Olson et al, 2005;Richard et al, 2011), and SERCA2a impairment is closely associated with decreased heart contractility in DOX cardiotoxicity (Frank et al, 2003;Periasamy & Huke, 2001). In this study, DOX treatment caused significant decrease (p50.05) of SERCA2a mRNA expression level in the DOX only-treated group which can partially explain the rise of cytosolic and mitochondrial calcium levels.…”
Section: Discussionmentioning
confidence: 50%
“…Several studies have proved that reactive oxygen species resulted from DOX treatment has either direct or indirect effect to calcium regulatory proteins (Arai et al, 1998;Olson et al, 2005;Richard et al, 2011). Arai et al (2000) demonstrated the effect of DOX to the expression and activity of SERCA2a, a calcium pump responsible for calcium influx from cytosol to sarcoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“…Using proliferating H9c2 cells, a suppression of HO1 expression has been reported after in vitro ANT treatment (Bernuzzi et al, 2009), whereas others have suggested the opposite in a microarray study (Choi et al, 2008). Little to no change in HO1 expression has been seen at protein and mRNA levels 2 weeks after a single supratherapeutic ANT dose (Suliman et al, 2007) and 70 days after injection of 1 mg/kg for 10 days (Richard et al, 2011), respectively. Piantadosi et al (2008 have also reported HO1 as an important checkpoint involved in the cross-talk between the Nrf2 pathway and mitochondrial biogenesis with the possibility of providing powerful cardioprotection against acute ANT cardiotoxicity induced by a single high dose of doxorubicin.…”
Section: Discussionmentioning
confidence: 98%